J. M. Bak, B. K. Király (wyd.), From Hunyadi to Rákóczi. War and society in late medieval and early modern Hungary - Russocki, Stanisław (Czasopismo Prawno-Historyczne, 1984)
Recenzja: From Hunyadi to Rákóczi. War and society in late medieval and early modern Hungary, ed. by Jánosz M. Bak, Béla K. Király, Brooklyn College Press distributed by Columbia University Press, 1982, ss. XIV, 545. Atlantic Studies. Studies in society in change no. 12, ed. Béla K. Király; East-European monographs no. CIV. War and society in East-central Europe, vol. III.